Measurement of Inflammation in Eosinophilic Esophagitis Using an Eosinophil Peroxidase Assay. (July 2016) - Saffari, Hedieh; Leiferman, Kristin M; Clayton, Frederic; Baer, Krista; Pease, Leonard F III; Gleich, Gerald J; Peterson, Kathryn A
Abstract : OBJECTIVES: We describe a simple, quick method to measure an eosinophil granule protein, eosinophil peroxidase (EPO), as a marker of eosinophil activity, in eosinophilic esophagitis (EoE). METHODS: Esophageal mucosal brushings initially were collected from 36 patients with active EoE ( n =13), resolved EoE ( n =13), and controls ( n =10) before endoscopic biopsy collection; the brushes were frozen at –80 ºC until assayed. EPO on the brush was measured in a colorimetric assay visually and by spectrophotometric absorbance measurements (at 492 nm), and was compared with peak eosinophil counts in esophageal biopsy specimens. The assay was calibrated with known EPO concentrations; as EPO increased in the assay, the color changed from light yellow to dark brown. RESULTS: Mucosal brush specimens from active EoE yielded orange to dark brown colors with absorbance measurements > 1.1 U; in contrast, control and resolved EoE brush specimens yielded a light to dark yellow color with absorbance measurements < 1.1. We then corroborated the results at the bedside (real time) in 16 additional patients. EPO on the brush was measured directly in < 1 h in the assay visually and by absorbance at 492 nm. Absorbance units strongly correlated with peak eosinophil counts both with the frozen brush ( rs =0.79, P <0.0001) and with the bedside (rs =0.86, P <0.00017) approaches. CONCLUSIONS: The results support the use of this rapid method to detect and monitor EoE disease activity. Moreover, because eosinophils infiltrate and degranulate in the esophagus in EoE in a patchy manner, this method may be more accurate than current practice by testing for an eosinophil constituent from both intact and degranulated cells, and by sampling large portions of the esophageal lumen rather than small biopsy specimens that may not be representative of eosinophil involvement.